The basic helix–loop–helix olig3 establishes the neural plate boundary of the trunk and is necessary for development of the dorsal spinal cord - Filippi, Alida (National Academy of Sciences, 2005)
olig genes encode a previously unrecognized group of vertebrate-specific basic helix–loop–helix transcription factors. As shown in mice, chickens, and zebrafish, two members of this group, olig1 and olig2, are involved in the differentiation of motoneurons and oligodendrocytes, but nothing is known about the role of the third member, olig3. Here, we show that olig3 plays an essential role in the establishment of the neural crest–lateral neural plate boundary. In zebrafish embryos, morpholino-induced olig3 inactivation dramatically increases the number of neural crest cells, but lateral neural plate fates (interneurons and astrocytes) are missing. Zebrafish swirl mutants that have impaired bone morphogenetic protein signaling and lack neural crest cells display an expanded olig3 expression domain. Moreover, olig3 is up-regulated in mindbomb mutants lacking the neural crest because of an impaired notch signaling, and olig3 repression in such mutants rescues the neural crest. In addition, olig3 regulates ngn1 and deltaA expression in interneuron precursors. Our results indicate that olig3 has an essential proneural activity in the dorsal spinal cord and cooperates with the Delta/Notch regulatory loop to establish the boundary between the neural crest and the lateral neural plate. Thus, a proper regulation of the olig gene family is essential for the formation of three cell types (oligodendrocytes, astrocytes, and neural crest) that are unique to vertebrates.